A Review of Gastric Polyps - Abu Taiub Mohammed Mohiuddin Chowdhury; Shuixiang He; Ru Hua Wang; Dan Guo; Yarui Li (Journal of Digestive Endoscopy, 2019)
Gastric lesions presenting as polyps becomes common these days. Many different underlying causes have been suspected with the origin of gastric polyps. Generally, a gastric polyp is considered as benign in the first impression unless proven otherwise. Though, they show a vast variety of malignant potentials. This literature is intended to describe and evaluate the variations, presentations, features, and potentials of gastric polypoid lesions.